USING THE INFORMATION GAP TECHNIQUE TO PROMOTE THE MOTIVATION OF THE EIGHTH GRADERS OF SMPN 3 PASURUAN TO SPEAK ENGLISH - Mushoffan Prasetiano (Universitas Potensi Utama, 2016)
The results of preliminary study in the eighth grade of SMPN 3 Pasuruan show that the junior high school students face some problems in speaking. Most of the students had low motivation to speak because they were afraid of making grammatical mistakes. To overcome the problems, the researcher implemented the information gap technique. This study adopted the Classroom Action Research (CAR) design proposed by Kemmis and Mc Taggart (1988). The results of the study show that the information gap technique met the criteria of success. The students’ level of motivation increased from low to fair. And 58% of students show an increase in the frequency of speaking from passive to active and 8.4% of students show an increase in the frequency of speaking from passive to very active. In this study, the researcher used real life materials, gave examples to clarify the instructions, informed the students of the learning objectives, and used group work instead of pair work.